Mucin Variable Number Tandem Repeat Polymorphisms and Severity of Cystic Fibrosis Lung Disease: Significant Association with MUC5AC - Guo, XueLiang (Public Library of Science, 2011)

(untitled)
Variability in cystic fibrosis (CF) lung disease is partially due to non-CFTR genetic modifiers. Mucin genes are very polymorphic, and mucins play a key role in the pathogenesis of CF lung disease; therefore, mucin genes are strong candidates as genetic modifiers. DNA from CF patients recruited for extremes of lung phenotype was analyzed by Southern blot or PCR to define variable number tandem repeat (VNTR) length polymorphisms for MUC1, MUC2, MUC5AC, and MUC7. VNTR length polymorphisms were tested for association with lung disease severity and for linkage disequilibrium (LD) with flanking single nucleotide polymorphisms (SNPs). No strong associations were found for MUC1, MUC2, or MUC7. A significant association was found between the overall distribution of MUC5AC VNTR length and CF lung disease severity (p = 0.025; n = 468 patients); plus, there was robust association of the specific 6.4 kb HinfI VNTR fragment with severity of lung disease (p = 6.2×10(−4) after Bonferroni correction). There was strong LD between MUC5AC VNTR length modes and flanking SNPs. The severity-associated 6.4 kb VNTR allele of MUC5AC was confirmed to be genetically distinct from the 6.3 kb allele, as it showed significantly stronger association with nearby SNPs. These data provide detailed respiratory mucin gene VNTR allele distributions in CF patients. Our data also show a novel link between the MUC5AC 6.4 kb VNTR allele and severity of CF lung disease. The LD pattern with surrounding SNPs suggests that the 6.4 kb allele contains, or is linked to, important functional genetic variation.